2020
DOI: 10.21203/rs.2.22235/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of multi-drug resistant Campylobacter spp. and residual antimicrobials at poultry farms and live bird markets in Bangladesh

Abstract: Background: Understanding potential risks of multi-drug resistant (MDR) pathogens from the booming poultry sector is a crucial public health concern. Campylobacter spp. are among the most important zoonotic pathogens associated with MDR infections in poultry and human. This study systematically examined potential risks and associated socio-environmental factors of MDR Campylobacter spp. in poultry farms and live bird markets (LBMs) of Bangladesh.Methods: Microbial culture and PCR-based methods were applied to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…in small scale commercial broiler farms (Alam et al, 2020), Campylobacter spp. in poultry farms and live bird markets (Neogi et al, 2020), Salmonella in small-scale commercial layer flocks (Haque et al, 2021), and Campylobacter species in ducks (Uddin, 2018). This phenomenon suggested that use of poultry litter in aquaculture might grow the antimicrobial resistance capacity for the pathogenic microbes in aquatic environments, which obviously will not be a wise idea for the practitioners and aquaculturists.…”
Section: Exposure Pathway Of Antibiotics In Aquaculturementioning
confidence: 99%
“…in small scale commercial broiler farms (Alam et al, 2020), Campylobacter spp. in poultry farms and live bird markets (Neogi et al, 2020), Salmonella in small-scale commercial layer flocks (Haque et al, 2021), and Campylobacter species in ducks (Uddin, 2018). This phenomenon suggested that use of poultry litter in aquaculture might grow the antimicrobial resistance capacity for the pathogenic microbes in aquatic environments, which obviously will not be a wise idea for the practitioners and aquaculturists.…”
Section: Exposure Pathway Of Antibiotics In Aquaculturementioning
confidence: 99%